Dampak UU Hubungan Keuangan Pemerintah Pusat Dan Daerah (UU HKPD) Terhadap Kebijakan Fiskal Pemerintah Daerah - Intan Rakhmawati; Wirawan Suhaedi; Tusta Citta Ihtisan Tri Prasidya; Heni Yulianingsih (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2026)
The enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (2022) brought changes to regional regulations on regional taxes. This was implemented to encourage the optimization of regional tax collection. This study aims to analyze whether the enactment of changes to district regulations on regional taxes has brought changes to regional tax collection and regional government fiscal policy. This research is necessary because similar research is still minimal, so it is hoped that it can provide suggestions towards better fiscal capacity. The research method was through interviews regarding changes in fiscal policy through regional regulations. Based on these results, it was continued with an analysis of documentation of regional regulations on regional taxes. Through this study, it is hoped that policy recommendations will be generated for the district Regional Revenue Agency (Bapenda) and the regional tax collection office. As a result, the Regional Governments of West Lombok Regency and Central Lombok Regency have adjusted their regional regulations. Changes in regional tax rates have brought changes to regional fiscal capacity as well as improved and more digitalized regional efforts for regional tax collection and reporting. However, the implementation of the HKPD Law has not had an impact on regional fiscal capacity.